2014
DOI: 10.1016/j.toxlet.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Skin permeation and metabolism of di(2-ethylhexyl) phthalate (DEHP)

Abstract: Phthalates are suspected to be endocrine disruptors. Di(2-ethylhexyl) phthalate (DEHP) is assumed to have low dermal absorption; however, previous in vitro skin permeation studies have shown large permeation differences. Our aims were to determine DEHP permeation parameters and assess extent of skin DEHP metabolism among workers highly exposed to these lipophilic, low volatile substances. Surgically removed skin from patients undergoing abdominoplasty was immediately dermatomed (800 μm) and mounted on flow-thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 43 publications
3
34
0
Order By: Relevance
“…For example, the transdermal absorbed rate for DEHP was comprehensively determined to be 20% from the animal tests and the like (Elsisi et al, 1989;Melnick et al, 1987;Ng et al, 1992), and the human permeation coefficient from the in vitro skin permeation test (Scott et al, 1987;Barber et al, 1992) was derived as 5% of the transdermal absorbed rate in humans, based on the knowledge that it is one-fourth of that in rats. However, it has been clarified in elaborate in vitro skin permeation tests using fresh human skin as currently reported that while DEHP itself does not permeate through skin, MEHP, which is gradually formed by hydrolysis of DEHP through esterase locally present on the epidermis, permeates through skin, and it has been reported that 100% of MEHP was detected in the receptor solution when DEHP in solution form was applied and that the permeation coefficient increased 20 times compared to that of the non-diluted form (Hopf et al, 2014). The measured value of the permeation coefficient is remarkably larger than the obtained value in human skin and the obtained value in experimental animals, and the transdermal absorbed rate in humans is important knowledge suggesting that it is clearly higher than the previously supposed rate.…”
Section: Phthalatesmentioning
confidence: 99%
“…For example, the transdermal absorbed rate for DEHP was comprehensively determined to be 20% from the animal tests and the like (Elsisi et al, 1989;Melnick et al, 1987;Ng et al, 1992), and the human permeation coefficient from the in vitro skin permeation test (Scott et al, 1987;Barber et al, 1992) was derived as 5% of the transdermal absorbed rate in humans, based on the knowledge that it is one-fourth of that in rats. However, it has been clarified in elaborate in vitro skin permeation tests using fresh human skin as currently reported that while DEHP itself does not permeate through skin, MEHP, which is gradually formed by hydrolysis of DEHP through esterase locally present on the epidermis, permeates through skin, and it has been reported that 100% of MEHP was detected in the receptor solution when DEHP in solution form was applied and that the permeation coefficient increased 20 times compared to that of the non-diluted form (Hopf et al, 2014). The measured value of the permeation coefficient is remarkably larger than the obtained value in human skin and the obtained value in experimental animals, and the transdermal absorbed rate in humans is important knowledge suggesting that it is clearly higher than the previously supposed rate.…”
Section: Phthalatesmentioning
confidence: 99%
“…Such as reported PAEs are not very volatile, but they readily form aerosols that may be inhaled in particular during work with high temperature processes [29]. In addition, dermal exposures could potentially play a role in low temperature operations; on the other hand, due to their chemical characteristics (lipophilicity), dermal phthalate absorption is assumed to below or negligible.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dermal exposures could potentially play a role in low temperature operations; on the other hand, due to their chemical characteristics (lipophilicity), dermal phthalate absorption is assumed to below or negligible. Several authors [29][30][31] claim that this theory might be not true because among phthalates exposed workers performing low temperature processes was found the presence of urinary PAEs metabolites. Gaudin [30] founds elevated urinary 5cx-MEPP metabolite concentrations (median 107.5 g/L) among workers preparing a DEHP-containing material at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Hopf et al (2014) reported recently that the softening plasticizer and suspected endocrine disruptor diethyl hexyl phthalate is completely hydrolysed to monoethyl hexyl phthalate by freshly excised human skin such that only this metabolite and an oxidative metabolite, 5-oxo-monoethy hexyl phthalate, derived from the primary metabolite penetrate through the skin into the receptor fluid.…”
Section: Xenobiotica-metabolizing Enzymes In the Human Skin Includingmentioning
confidence: 99%